2022
DOI: 10.1159/000521251
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Older Adults’ E-Health Information-Seeking Behaviors

Abstract: <b><i>Introduction:</i></b> The Internet is an important source for health information and a medium for older adults’ empowerment in health decision-making and self-caring. Therefore, we aimed to identify the potential motivators and probable barriers of e-health information-seeking behaviors (e-HISB) among older Iranian adults. <b><i>Methods:</i></b> A cross-sectional study assessed the usefulness of self-efficacy, perceived encouragement, positive attitude towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…E-Health literacy is defined as the ability to find, understand, and appraise health information from electronic resources and apply that knowledge to making a health-related decision [ 20 ]. Pourrazavi et al [ 6 ] consider that e-Health literacy is one of the major barriers of senior adults to have e-Health information-seeking behaviors (e-HISB). The construct of e-Health literacy combines six forms of literacy, namely, traditional, information, media, health, scientific and computer [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…E-Health literacy is defined as the ability to find, understand, and appraise health information from electronic resources and apply that knowledge to making a health-related decision [ 20 ]. Pourrazavi et al [ 6 ] consider that e-Health literacy is one of the major barriers of senior adults to have e-Health information-seeking behaviors (e-HISB). The construct of e-Health literacy combines six forms of literacy, namely, traditional, information, media, health, scientific and computer [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, because of economic interests or lack of control, the media makes the audience suffer from false health information [ 4 , 5 ]. Therefore, facing the technological risks in this media society, especially in the era of social media, Internet users need to develop digital literacy, information literacy, health literacy as well as certain health information behavior abilities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Internet use can also facilitate access to health information for the elderly, thus improving their health literacy [ 5 ]. Coupled with the massive demand for internet use brought about by the COVID-19 outbreak, increasing internet usage among the elderly has become a priority [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, receiving information through associations, telephone systems, and newspapers/magazines has been the least behavior. It is suggested that health policymakers and managers provide facilities and budget and develop an appropriate program to improve these methods practically and cost-effectively ( Pourrazavi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%